Adaptation to climate change in Asia - Vachani, Susshil; Usmani, Jawed (Edward Elgar, 2014)
The frequency and scale of damage inflicted by climate-related disasters, including floods, drought, heat waves and hurricanes, has been increasing at an alarming rate. This volume provides a timely and thoughtful discussion of strategies for adaptation to climate change, which can complement mitigation strategies being developed by other experts throughout the world. The book focuses on eight geographically diverse territories in Asia, which are among the areas that will experience the most severe impacts of climate change and are the most vulnerable in terms of capacity to cope with the damage. The authors discuss adaptation strategies to safeguard food and water supplies, address urban problems, support migrant workers, protect coastal cities and preserve biodiversity. They also offer a critical analysis of plans that have proven successful to explore what additional steps can be taken to address the gaps. The collection of observations and recommendations in this book will prove invaluable to policy makers in countries that are facing similar threats and looking to build their adaptive capacity to cope with climate change. It will also appeal to academics interested in environmental ecology, sustainable development, global climate change and Asian studies.--Source other than Library of Congress.